The Immunopathology of COVID-19 and the Cannabis Paradigm - Paland, Nicole; Pechkovsky, Antonina; Aswad, Miran; Hamza, Haya; Popov, Tania; Shahar, Eduardo; Louria-Hayon, Igal (Frontiers in Immunology, 2021)
Abstract Coronavirus disease-19 caused by the novel RNA betacoronavirus SARS-CoV2 has first emerged in Wuhan, China in December 2019, and since then developed into a worldwide pandemic with > 99 million people afflicted and > 2.1 million fatal outcomes as of 24th January 2021. SARS-CoV2 targets the lower respiratory tract system leading to pneumonia with fever, cough, and dyspnea. Most patients develop only mild symptoms. However, a certain percentage develop severe symptoms with dyspnea, hypoxia and lung involvement which can further progress to a critical stage where respiratory support due to respiratory failure is required. Most of the COVID-19 symptoms are related to hyperinflammation as seen in cytokine release syndrome and it is believed that fatalities are due to a COVID-19 related cytokine storm. Treatments with anti-inflammatory or anti-viral drugs are still in clinical trials or could not reduce mortality. This makes it necessary to develop novel anti-inflammatory therapies. Recently, the therapeutic potential of phytocannabinoids, the unique active compounds of the Cannabis plant, has been discovered in the area of immunology. Phytocannabinoids are a group of terpenophenolic compounds which biological functions are conveyed by their interactions with the endocannabinoid system in humans. Here, we explore the anti-inflammatory function of cannabinoids in relation to inflammatory events that happen during severe COVID-19 disease, and how cannabinoids might help to prevent the progression from mild to severe disease.